Bulgaria : Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2004)
Bulgaria's request for a 25-month precautionary Stand-By Arrangement (SBA) in an amount of SDR 100 million or 15.62 percent of quota is discussed. The SBA-supported program seeks to reduce increased external vulnerability and to achieve sustainable high growth through a tighter fiscal policy and measures to drain bank liquidity to reduce excess demand in the short term and structural reforms to boost output and export capacity in the medium term.